Evangelism as Storytelling: A Reconstruction of Evangelism from a Feminist Postcolonial Missiological Perspective: Oleh Oinike Natalia Harefa - Simatupang, Anita Rushadi (Indonesian Journal of Theology, 2024)
A book review of Evangelism as Storytelling: A Reconstruction of Evangelism from a Feminist Postcolonial Missiological Perspective.